FOR THE GENESIS OF INTERVIEW AS A GENRE - Natsvlishvili, Paata (European Scientific Journal, ESJ, 2014)
The word â€˜interviewâ€™ was first introduced in 1867 and appeared in the OED in 1869. The first examples of interview as a means of spreading information via press date to no earlier than 1830s. So, the discovery of dialogues, included in old Georgian text, which fully comply with criteria of journalistic interviewâ€™s matrix, is worthy of serious study. â€œMimoslvaâ€ is a travel essay written in 1750s by Archbishop Timothy Gabashvili (1704- 1764), prominent Georgian religious figure, diplomat, writer and traveler. In some parts of the essay it is apparent that Gabashvili is playing the role of interviewer. And the main interviewee is Eugenios Boulgaris (1716-1806), renowned Greek theologian, Rector of famous Orthodox School of Mount Athos. Nowadays, for journalism as a creative act, adequate up-to-date technology is of vital importance, but it becomes insignificant when it comes to the first samples of journalism. The same can be stated regarding Gabashviliâ€™s interview. At the time when the interview was conducted (1756), Gabashvili was able to produce his text only as a manuscript which is the form in which it eventually appeared. So, the text was realized. It should be mentioned that the first edition of Gabashviliâ€™s work (1852) chronologically precedes the first samples of complete interviews and the word â€˜interviewâ€™ itself. In conclusion, in the light of the archeology of journalism, I suggest that until the discovery of an older example that would fit the matrix of interview-as-genre, Gabashviliâ€™s interview should be deemed as the oldest interview in the history of journalism.